Dynamic effects of fiscal policy on output and unemployment in Nigeria: An econometric investigation - Attahir B. Abubakar (CBN Journal of Applied Statistics, 2016)
This study investigates the effect of fiscal policy shocks on output and unemployment in Nigeria under the Keynesian framework by employing the Structural Vector Autoregression (SVAR) methodology to analyse annual series on the relevant variables for the period 1981-2015. Augmented Dickey Fuller (ADF) test for unit root result shows all variables to be integrated of order one and Johansen Cointegration test confirms the presence of long run association among the variables. Findings of the SVAR model shows shock in public expenditure as having a positive long- lasting effect on output. Revenue shock was found to exert a positive effect (lower than that of public expenditure shock) on output. However, the effect of revenue shock on unemployment was found to be negative but short-lived. The study suggested that government should restructure its spending pattern by allocating more to productive expenditure. In the same vein, it was suggested that government should harness its revenue potentials by expanding its revenue base via effective and efficient taxation system and also through diversification of its revenue base.
Keywords: H20; H30; H50; 330; Economic growth; fiscal policy; output; unemployment; Nigeria